A blow-up criterion for the full compressible Euler–Maxwell system. (July 2016) - Fan, Jishan; Li, Fucai; Nakamura, Gen
Abstract: In this note we prove a blow-up criterion for the full compressible Euler–Maxwell system in R 3 .